On-line redox speciation analysis of antimony using L-proline immobilized on controlled pore glass and hydride generation inductively coupled plasma optical emission spectrometry for detection - Menegario, Amauri A.; Smichowski, Patricia; Tonello, Paulo S. [UNESP]; Polla, Griselda; Oliveira, Eliane P.; Santelli, Ricardo E. (Elsevier B.V., 2008)
L-proline was immobilized on controlled pore glass to study the ability of this material for the separation and preconcentration of Sb(III) and Sb(V). The substrate was packed in a minicolumn and incorporated in a flow injection system. The effluents of the on-line solid phase extraction (before and after elution) were directly coupled to the hydride generation inductively coupled plasma optical emission spectrometry system. The effect of pH, sample (and eluent) volume, flow rates of sample loading and elution on separation of Sb(III) e Sb(V) were evaluated. Our experiments demonstrated that Sb(V) was not retained and it was selectively determined during the loading step, while retained Sb(III) was determined afterelution. The proposed system was also used for the selective preconcentration of Sb(III). In this case, a preconcentration factor of 11 and a limit of detection of 90 ng L-1 for Sb(III) were achieved when 8 mL of sample were loaded into the column. The speciation analysis of inorganic Sb in river water and effluent samples was performed using the proposed method. The values obtained for total Sb (obtained by sum of Sb(III) and Sb(V)) were in good agreement with expected values. Recoveries of Sb(III) and Sb(V) in the river water Standard Reference Material 1640 (from National Institute of Standard and Technology) and spiked river waters were between 83 and 111%. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: antimony; L-proline; speciation analysis; controlled pore glass; hydride generation